A comprehensive analysis of dementia cerebrospinal fluid biomarkers using GWAs, polygenic risk scores and Mendelian randomization in Parkinson's disease: Genetics/atypical and other dementias. (7th December 2020) - Ibanez, Laura; Bahena, Jorge Alberto; Dube, Umber; Farias, Fabiana H.G.; Yang, Chengran; Harari, Oscar; Cruchaga, Carlos; Benitez, Bruno A.
Abstract: Background: Cerebrospinal fluid (CSF) levels of amyloid beta (Aβ), tau and p‐tau are the standard biomarkers for diagnosis and progression of Alzheimer disease (AD). CSF levels of Alpha‐synuclein (α‐Syn) have not been very informative in Parkinson's disease (PD). The burden of Aβ plaques and Tau tangles inversely correlates with cognitive status in PD cases with dementia. However. Lewy body aggregated correlates with dementia progression in PD. A systematic study of CSF biomarkers in PD is yet to be complete, thus, we aimed to investigate the relationship between dementia biomarkers and PD using polygenic risk scores and Mendelian Randomization. Methods: Genome wide association analyses (GWAs) were performed in N = 1, 960 individuals to define the genetic architecture of CSF biomarker levels (α‐syn, Aβ, tau and p‐tau). CSF values were normalized using Z‐score; linear regression was corrected by sex, age and population structure. We performed the same analyses in PD affected individuals only (N = 700) to evaluate if the signals were driven by the PD population. PD genetic architecture was obtained from the latest PD risk meta‐analysis (Nalls, et al 2019) summary statistics. . Results: PRS analysis showed that CSF Aβ genetic architecture was correlated to that of PD (p = 2.5 × 10 −11 ; R 2  = 2.29%.), but not α‐syn, tau or p‐tau. Mendelian randomization methods found that CSF Aβ have a causal role in PD (p = 1.44 × 10 −05 ); an effect mediated by a SNP near the APOE gene (rs769449). Additionally, a trend towards a causal association was found for α‐Syn and PD (p = 0.06). GWAs on PD only population did not reveal any new or known signal for those CSF proteins. Conclusion: We demonstrated that Aβ is involved in the causal pathway of PD, even though APOE does not seem to be related to CSF Aβ levels or PD risk in PD cohorts. α‐Syn also seems to have a causal relation with PD, but studies with a larger number of samples are needed.